German Policy Towards Muslim Communities - L. R. Sadykova (Vestnik MGIMO-Universiteta)
The past two-three decades can be characterized by the period of global migration and sharp jump of migratory streams is connected with globalization and with the economic factor, generating labor movement behind resources from Third World countries to the countries with deficiency of labor. The desire to receive comfort life becomes the major reason, and the migrant makes the decision being guided by private interest more often instead of external factors. Western Europe became one of the most important center of gravity of migrants. During the post-war period the need of Europe in foreign labor for restoration of the economy destroyed by war, laid the foundation of mass international migration to this region. Globalization of migratory streams, penetration of foreign culture groups into structure of accepting society and prevalence of multicultural, multiethnic societies are important characteristics of a modern era. Western Europe became one of the most important centers of gravity of migrants. During the post-war period, the need of Europe in foreign labor for restoration of the economy destroyed by war laid the foundation of mass international migration to this region. Special relevance the problem of reception of immigrants, in particular from the Muslim countries, got for the former colonial powers, in particular Great Britain, France, and the Netherlands. Germany also faced this problem; migrants workers from other countries were required for the post-war restoration. Now Germany still is one of the main centers of an attraction of migrants, and concentration of them in this country annually increases. Despite the steps taken by the German government on elimination of Muslim isolation in the German society, its efforts did not bear fruits so far. The majority of Muslims live their life and are still torn off from high life of the country. A possible threat of destruction of the German community appeared when the various ethnic groups appeared in the country.